2019
DOI: 10.2147/iprp.s181213
|View full text |Cite
|
Sign up to set email alerts
|

<p>How to identify, assess, and refer patients experiencing interpersonal violence across the lifespan: the role of US pharmacists in integrated pharmacy research and practice</p>

Abstract: Interpersonal violence is a public health crisis in need of multipronged interventions. Victims of violence experience both acute injuries and chronic illness and may seek acute self-care and/or have the need for chronic medication therapy. Thus, the community-based, ambulatory pharmacy setting can serve as a portal for identification of, and intervention for, victims of violence. This article provides background on four types of interpersonal violence, including intimate partner, child and elder abuse, in add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…A previous examination of the role of pharmacists reported on compendiums of statutes related to reporting, but did not conduct a new search of statutes and legislation. 25 To the best of our knowledge, the current project is the first to comprehensively report violence and abuse reporting requirements for pharmacists. There is a need for future studies to examine how to prepare pharmacists to best serve patients experiencing interpersonal violence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous examination of the role of pharmacists reported on compendiums of statutes related to reporting, but did not conduct a new search of statutes and legislation. 25 To the best of our knowledge, the current project is the first to comprehensively report violence and abuse reporting requirements for pharmacists. There is a need for future studies to examine how to prepare pharmacists to best serve patients experiencing interpersonal violence.…”
Section: Discussionmentioning
confidence: 99%
“…3,24 As has recently been reported, there is no comprehensive database of U.S. laws regarding pharmacist mandatory reporting requirements related to violence and abuse. 25…”
mentioning
confidence: 99%
“…Two exploratory studies with US pharmacy professionals and clients found that there is a potential for pharmacybased identification and response to DSVA. 42 The studies of pharmacists' and clients' perspectives on providing public health services 43,44 and exploratory studies on identifying and responding to DSVA in pharmacies 30,33…”
Section: What Is Already Known On This Topicmentioning
confidence: 99%
“…To frame readings of the past, researchers often acknowledge the alternate historicities of past authors, while simultaneously placing them within linear models that conform to their own present realities. 16 Walter Benjamin called this the historicist's "stream of becoming." He decried this method for presuming to order past events as things actually happened, when really the scholar toggles back and forth across time, producing "anachronistic assemblages" of "restoration and reestablishment" that are always "imperfect and incomplete" but packaged as scholarship.…”
Section: What We Have and What We Say About Itmentioning
confidence: 99%